2016
DOI: 10.4172/2475-319x.1000101
|View full text |Cite
|
Sign up to set email alerts
|

Life-Course-Persistent Antisocial Behavior

Abstract: The article reviewed the status of the Life Course Persistent category of antisocial behavior some two decades plus from its original formulation as well as the finding from the landmark Dunedin longitudinal study of antisocial behavior that this category is comprised almost entirely of males. The importance of this category for forensic psychology is the robust and remarkable finding that the small group of individuals (5-10%) who tend to cluster in this category are responsible for over half of all crimes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Some studies have shown that substance use and depressive symptoms in adolescents may increase the likelihood of displaying antisocial behaviours (Hemphill et al, 2015; Park et al, 2010). In addition, age has a significant impact on antisocial behaviours in that the period of adolescence is associated with a significantly higher degree of antisocial behaviours compared to other phases in an individual’s lifespan (Eme, 2016; Henry et al, 1993). Although all our participants were adolescents, the age range was quite large (13–21), and thus it was necessary to control for age.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have shown that substance use and depressive symptoms in adolescents may increase the likelihood of displaying antisocial behaviours (Hemphill et al, 2015; Park et al, 2010). In addition, age has a significant impact on antisocial behaviours in that the period of adolescence is associated with a significantly higher degree of antisocial behaviours compared to other phases in an individual’s lifespan (Eme, 2016; Henry et al, 1993). Although all our participants were adolescents, the age range was quite large (13–21), and thus it was necessary to control for age.…”
Section: Methodsmentioning
confidence: 99%
“…Criminality along the life span tends to follow a normal curve, peaking around Age 16 and declining in late adolescence or early adulthood, a pattern known as the age-crime curve (Hirschi & Gottfredson, 1983; Nagin, 2016). Rather than an abrupt cessation of offending, desistance is an extended process of lower-level offending before cessation occurs (DeLisi & Piquero, 2011; Eme, 2016). Data from the Cambridge Study in Delinquent Development suggest that offenders typically “age out” of crime between Ages 20 and 30 (Jennings, Rocque, Fox, Piquero, & Farrington, 2016).…”
Section: Step 1: Default Assumption—most Offenders Desist From Crimin...mentioning
confidence: 99%
“…Schumacher and Kurz (1999) replicated these results, finding 8% of juvenile offenders accounted for approximately 60% of criminal cases. Recent estimates place the percentage of life-course persistent juvenile offenders at 3–10% (DeLisi, 2016; Eme, 2016; Nagin, 2016). Taken together, research suggests a small proportion of juvenile offenders (3–10%) will offend across the life span.…”
Section: Step 2: Adjust From the Base Rate If The Juvenile Appears To...mentioning
confidence: 99%
See 2 more Smart Citations